Network meta‐analysis of randomized trials in multiple myeloma: Efficacy and safety in frontline therapy for patients not eligible for transplant. Issue 5 (11th July 2022) - Botta, Cirino; Gigliotta, Emilia; Paiva, Bruno; Anselmo, Rita; Santoro, Marco; Otero, Paula Rodriguez; Carlisi, Melania; Conticello, Concetta; Romano, Alessandra; Solimando, Antonio Giovanni; Cerchione, Claudio; Vià, Matteo Da; et al.
Abstract: The treatment scenario for newly‐diagnosed transplant‐ineligible multiple myeloma patients (NEMM) is quickly evolving. Currently, combinations of proteasome inhibitors and/or immunomodulatory drugs +/− the monoclonal antibody Daratumumab are used for first‐line treatment, even if head‐to‐head comparisons are lacking. To compare efficacy and safety of these regimens, we performed a network meta‐analysis of 27 phase 2/3 randomized trials including a total of 12, 935 patients and 23 different schedules. Four efficacy/outcome and one safety indicators were extracted and integrated to obtain (for each treatment) the surface under the cumulative ranking‐curve (SUCRA), a metric used to build a ranking chart. With a mean SUCRA of 83.8 and 80.08 respectively, VMP + Daratumumab (DrVMP) and Rd + Daratumumab (DrRd) reached the top of the chart. However, SUCRA is designed to work for single outcomes. To overcome this limitation, we undertook a dimensionality reduction approach through a principal component analysis, that unbiasedly grouped the 23 regimens into three different subgroups. On the bases of our results, we demonstrated that first line treatment for NEMM should be based on DrRd (most active, but continuous treatment), DrVMP (quite "fixed‐time" treatment), or, alternatively, VRD and that, surprisingly, melphalan as well as Rd doublets still deserve a role in this setting.